Biphenyl hydrogenation over supported transition metal catalysts under supercritical carbon dioxide solvent - Hiyoshi, Norihito; Rode, C. V.; Sato, O.; Shirai, M. (Applied Catalysis A - General, 2005)
Catalytic hydrogenation of biphenyl to bicyclohexyl, an organic hydrogen storage medium, was examined over supported transition metal catalysts in supercritical carbon dioxide solvent. The yield of bicyclohexyl was almost 100% over the charcoal-supported rhodium (Rh/C) and ruthenium (Ru/C) catalysts at the temperature of 323 K, which was much lower than that required for biphenyl hydrogenation in organic solvents (573 K). The initial activity was higher over the Rh/C catalyst, while the initial selectivity to bicyclohexyl was higher over the Ru/C catalyst. The conversion of biphenyl increased with increase in hydrogen and carbon dioxide pressures, while the selectivity to bicyclohexyl was independent of hydrogen and carbon dioxide pressures over both catalysts. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: bicyclohexyl; biphenyl; charcoal-supported rhodium catalyst; charcoal-supported ruthenium catalyst; Hydrogen storage; Hydrogenation; Supercritical carbon dioxide

Stereoselective hydrogenation of tert-butylphenols over charcoal-supported rhodium catalyst in supercritical carbon dioxide solvent - Hiyoshi, Norihito; Rode, Chandrashekhar V.; Sato, Osamu; Tetsuka, Hiroyuki; Shirai, Masayuki (Journal of Catalysis, 2007)
Hydrogenation of 2-, 3-, and 4-tert-butylphenols was studied over a charcoal- supported rhodium catalyst in supercritical carbon dioxide (scCO(2)) solvent, and the results were compared with those in organic solvents. In the hydrogenation of 4-tert-butylphenol, a higher cis ratio for 4-tert-butylcyclohexanol (0.79) was obtained in scCO(2) (10 MPa) than in 2-propanol (0.70) and cyclohexane (0.64) under similar conditions of hydrogen pressure (2 MPa) and temperature (313 K). In the case of 2-tert-butylphenol, the cis ratio for 2-tert-butylcyclohexanol was as high as 0.95 in both scCO(2) and 2-propanol (hydrogen pressure, 2 MPa; reaction temperature, 313 K). In the case of hydrogenation of 3-tert-butylphenol, the cis ratio decreased with the progression of consecutive hydrogenation of 3-tert-butylcyclohexanone intermediate. In addition, the stereoselectivity to cis-tert-butylcyclohexanols in scCO(2) was improved in the presence of hydrochloric acid. It was found that the protons of hydrochloric acid accelerated the hydrogenation of the intermediates, tert-butylcyclohexanones, to the corresponding cis-tert-butylcyclohexanols. The hydrogenation mechanism of tert-butylphenols, particularly the enhanced selectivity to cis-tert-butylcyclohexanols in scCO(2), is postulated based on the observed reaction profiles. (c) 2007 Elsevier Inc. All rights reserved.
Keywords: charcoal-supported rhodium catalyst; stereoselective hydrogenation; supercritical carbon dioxide solvent; tert-butylcyclohexanol